Grass straw mulching to suppress emergence and early growth of weeds - Oliveira Jr,R.S. (2014)
Sorghum, pearl millet, and Brachiaria ruziziensis have similar characteristics which have led to their use for mulch formation in no-till systems. This study was carried out to evaluate the potential of these three species as straw suppliers to suppress weed emergence. Initial findings led to the conclusion that both pearl millet and Brachiaria ruziziensis have similar or superior potential as weed suppressors, compared to sorghum straw, a species with recognized allelopathic potential. Subsequently, new trials were conducted under greenhouse conditions by sowing weed species in pots, followed by covering of the soil with the straw under evaluation. Independent experiments were conducted for Euphorbia heterophylla and Bidens pilosa. In each experiment, the factors analyzed were type of straw (pearl millet and B. ruziziensis), amount of straw (equivalent to 4 and 8 t ha-1 dry mass) and irrigation method (surface and subsurface). Both pearl millet and B. ruziziensis have shown to be species that can be cultivated to produce straw with allelopathic potential. These effects were effective in suppressing the emergence or early growth of E. heterophylla and B. pilosa. There was no difference in the suppression of emergence of these species when the soil cover level was alternated between 4 and 8 t ha-1 dry mass.